Kemampuan motorik kasar siswa sekolah dasar penderita obesitas - Isti Dwi Puspita Wati; Woro Kushartanti; Joko Susilo (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: Childhood is the period of rapid growth and development. Various aspects can affect problems in growth and development such as genetics, natural environment, and social economic status of the family, nutrition status, social and cultural environment. Inappropriate food intake can cause malnutrition in children, both undernourishment and over nourishment (obesity). Obesity is not good for the process of child growth and development because it distorts the process of metabolism and bring risks for cardiovascular diseases.Objective: To identify gross motor ability of obese elementary school students at Yogyakarta Municipality and evaluate motor ability of elementary school students based on degree of obesity.Method: The study was observational with cross sectional design. Subject of the study were 158 obese elementary school students at Yogyakarta Municipality. Subjects were screened and tested using fat caliper and their height and weight were measured. If they belonged to obese their gross motor ability was tested comprising throwing with target, flexibility long jump standing, squatting, push up, balance and speed running. Data were analyzed using Spearman correlation at CI95% (p<0.05).Result: Gross motor ability of children has negative correlation with obesity (r = -0,465), so children with heavy obesity rho have the bad gross motor ability. However there was no relationship between ability of flexibility, standing long jump, balance, and speed running the mobility (sig > 0,05).Conclusion: Child which progressively obesity will have a lower gross motor ability.